1992
DOI: 10.1063/1.107837
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence for the amorphous silicon phase in visible photoluminescent porous silicon

Abstract: We report on micro-Raman spectroscopy studies of porous silicon which show an 'amorphous silicon Raman line at 480 R cm-' from regions that emit visible photoluminescence. A Raman line corresponding to microcrystalline silicon at 510 R cm-' is also observed. X-ray photoelectron spectroscopy data is presented which shows a high silicon-dioxide content in porous silicon consistent with an amorphous silicon phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(36 citation statements)
references
References 13 publications
2
34
0
Order By: Relevance
“…The result [20] which suggests that a high percentage of this material is, indeed, present in the composition of the n-PS columns [4,21]. The results of this best fit is shown in Fig.…”
mentioning
confidence: 71%
“…The result [20] which suggests that a high percentage of this material is, indeed, present in the composition of the n-PS columns [4,21]. The results of this best fit is shown in Fig.…”
mentioning
confidence: 71%
“…After annealing at 400°C siloxene has an attractive luminescent property similar to porous silicon (Stathis & Kastner , 1987) . d. Structurally disordered phases: A significant amount of amorphous silicon was reported to contain within porous silicon (Perez et al, 1992). It is known that hydrogenated amorphous silicon (a-Si:H) can produce visible PL (Vasquez, 1985) and so it was suggested that a-Si:H might be responsible for 'red' PL band (Vasquez et al 1992) The observed tunability of the PL was further suggested as due to introduction of hydrogen into the amorphous silicon in varying amounts (Cullis & Canham,1991).…”
Section: Photoluminescencementioning
confidence: 99%
“…Since the initial work of Canham [1] on porous Si prepared by anodization of Si wafers, several workers have reported their experimental results on the fabrication methods [2][3][4], structural characterization [5,6] and optical properties [7][8][9] of nano-and micro-crystals. The PL properties of Si [7,10] and Ge [11] prepared by various methods have also been reported.…”
Section: Introductionmentioning
confidence: 99%